2011
DOI: 10.1074/jbc.m111.280552
|View full text |Cite
|
Sign up to set email alerts
|

Members of the Salivary Gland Surface Protein (SGS) Family Are Major Immunogenic Components of Mosquito Saliva

Abstract: Background: During feeding, mosquito saliva modulates the vertebrate host's hemostasis and inflammation response. Results: Anopheles gambiae Sgs4 and Sgs5 are major immunogenic proteins in mosquito saliva. Conclusion: Sgs4 and Sgs5 appear to play an essential role in blood feeding. Significance: Sgs4 and Sgs5 could serve as markers of human exposure to mosquito bites and in the development of disease control strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 55 publications
1
42
0
2
Order By: Relevance
“…It is plausible that during transmission of complex eukaryotic pathogens, such as Plasmodium, mosquito saliva affects immunogenicity but not infectivity, whereas during viral transmission the immune modulatory effects are broader. The recent identification of two major immunogenic salivary gland proteins provides a molecular framework to gain a better understanding of immune modulation by mosquito saliva (65). Alternatively, differences in the antigenic repertoire or in shedding of antigenic surface proteins during transmigration between hemocoel and salivary gland sporozoites might contribute to dissimilar immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that during transmission of complex eukaryotic pathogens, such as Plasmodium, mosquito saliva affects immunogenicity but not infectivity, whereas during viral transmission the immune modulatory effects are broader. The recent identification of two major immunogenic salivary gland proteins provides a molecular framework to gain a better understanding of immune modulation by mosquito saliva (65). Alternatively, differences in the antigenic repertoire or in shedding of antigenic surface proteins during transmigration between hemocoel and salivary gland sporozoites might contribute to dissimilar immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, in a study in Senegal, children who experienced low and moderate exposure exhibited decreased antibody concentrations clearly after more than 3 months (10) . Another study showed that the IgG antibody response to salivary gland proteins appearing after exposure to mosquito bites lasts 3-6 weeks (8) . Although the duration of the IgG response to salivary gland proteins may be brief (between 1 and 4 months), this response can detect specifi c proteins of the salivary gland, i.e., gSG6, in children exposed to very infrequent Anopheles bites.…”
Section: Immunogenic Proteins Found In Anopheles Sundaicus Salivary Gmentioning
confidence: 99%
“…Many studies have been conducted to identify and characterize immunogenic salivary proteins from malaria vectors in Africa; however, malaria vectors in Asia, particularly An. sundaicus, have not been studied (8) (17) (18) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest here, Anopheles antigens are known humoral immune targets; antibody titers against mosquito salivary gland extracts are even indicative of mosquito biting intensity (18). Constituent salivary gland proteins are increasingly well identified (19), and some proteins, such as salivary gland protein-4 and -5, are known antibody targets (20). Aside from humoral immunity, A. stephensi bites also activate mast cells and contribute to T cell hyperplasia in lymph nodes (21).…”
mentioning
confidence: 99%